2013
DOI: 10.1108/mhrj-02-2013-0007
|View full text |Cite
|
Sign up to set email alerts
|

Gardening as a mental health intervention: a review

Abstract: Purpose -The number of gardening-based mental health interventions is increasing, yet when the literature was last reviewed in 2003, limited evidence of their effectiveness was identified. The purpose of this paper is to evaluate the current evidence-base for gardening-based mental health interventions and projects through examining their reported benefits and the quality of research in this field. Design/methodology/approach -Studies evaluating the benefits of gardening-based interventions for adults experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
150
2
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 226 publications
(170 citation statements)
references
References 38 publications
10
150
2
8
Order By: Relevance
“…themes to emerge were "a space of one's own, meaningful activity, increased feelings of connectedness and improved physical and mental health" (Webber, Hinds, & Camic, 2015, p. 20). A review of studies on gardening as a mental health intervention found benefits across emotional, social, vocational, physical and spiritual domains (Clatworthy, Hinds, & Camic, 2013). A national UK review demonstrated that green gyms had the greatest impact on participants with the lowest physical health on joining who were nine times more likely to improve whereas those with the lowest mental health were three times more likely to improve (Yerrell, 2008).…”
Section: Models Of Social Prescribingmentioning
confidence: 99%
“…themes to emerge were "a space of one's own, meaningful activity, increased feelings of connectedness and improved physical and mental health" (Webber, Hinds, & Camic, 2015, p. 20). A review of studies on gardening as a mental health intervention found benefits across emotional, social, vocational, physical and spiritual domains (Clatworthy, Hinds, & Camic, 2013). A national UK review demonstrated that green gyms had the greatest impact on participants with the lowest physical health on joining who were nine times more likely to improve whereas those with the lowest mental health were three times more likely to improve (Yerrell, 2008).…”
Section: Models Of Social Prescribingmentioning
confidence: 99%
“…The four intervention studies described above had a particular focus on either animal-assisted or therapeutic horticulture interventions, since previous research indicates the mental health benefits of these kind of interventions [56][57][58]. Even though nature experiences and activity connected to animals and/or horticulture are important at care farms, the studies do not examine all components of the care farm context, as care farming programs in Norway are complex in nature.…”
Section: Recommendations For Further Researchmentioning
confidence: 99%
“…The majority of the literature on gardening and horticultural therapy is observational and subjective, and does little to advance understanding of the mechanisms for the therapeutic benefits of gardening. However, a growing number of quantitative studies involving diverse populations and a host of different gardening and horticultural activities have, in general, reported improvements in mental health status of study subjects (Clatworthy et al, 2013). More specifically, studies have reported reductions in anxiety (Lee et al, 2004;Kam and Siu, 2010;Gonzalez et al, 2011b), depression (Gonzalez et al, 2011a;Wilson and Christensen, 2011), negative mood state (Wichrowski et al, 2005;Kam and Siu, 2010;Van Den Berg and Custers, 2011), and perceived stress (Kam and Siu, 2010;Yun and Choi, 2010;Kotozaki et al 2015).…”
Section: People-plant Interactions Context and Backgroundmentioning
confidence: 99%
“…Therefore, space farming or gardening may offer a treatment modality that reduces the decline of crew mental health and well-being. A rigorous critical assessment of the evidence-based research on gardening as a mental health intervention was conducted by Clatworthy and colleagues for the years 2003-2013 (Clatworthy et al, 2013). From a list of 156 references produced by systematic search, just ten studies met four standards: 1, providing an empirical evaluation of an intervention involving active gardening; 2, adult participants experiencing functional mental health difficulties; 3, published in a peer-reviewed journal; and 4, written in English (Son et al, 2004;Stepney and Davis, 2004;Parr, 2007;Rappe et al, 2008;Gonzalez et al, 2009;2011a;Kam and Siu, 2010;Parkinson et al, 2011).…”
Section: Behavioral and Cognitive Benefits Of Gardeningmentioning
confidence: 99%